Potential impacts of an El Niño related drought on sweet potato consumption and prices in Papua New Guinea - Joseph, Josiah; Hayoge, Glen; Sikas-Iha, Helmtrude; Dorosh, Paul A.; Schmidt, Emily; Kedir Jemal, Mekamu (International Food Policy Research Institute, 2024)
Sweet potato plays an important role in the food system of Papua New Guinea (PNG), accounting for over 12 percent of total calories consumed in the country (IFPRI,2023). Three-quarters of sweet potato production takes place in the highlands where it is harvested throughout the year (Chang et al., 2013). However, the production and consumption of sweet potatoes in PNG faces several challenges, including climate change, pests and diseases, and market access constraints. In particular, a significant decline in sweet potato production due to an El Niño-related drought in early 2024 is a realistic possibility.